Os efeitos do Programa Bolsa Família sobre a frequência escolar das m\~aes adolescentes beneficiadas - Felícia Santos; Carlos Henrique Corseuil (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The paper assess the effect of the Brazilian Conditional Cash Transfer Program, Bolsa Familia (BF), on school attendance among adolescent mothers relative to adolescent non-mothers, combining quantitative and qualitative technics. The quantitative analysis was based on the 2010 Census, and was conducted in two steps. First we estimated through logit models the impact of maternity on schooling attendance for each one of the 138 Brazilian meso-regions. Then we used a linear model at the meso-region level to estimate the relationship between the incidence of BF on one hand, and the previously estimated sensibility of the schooling attendance to maternity on the other hand. The results indicate that BF increases relative less the schooling attendance among adolescent mothers. Semi structured interviews with adolescent mothers living in Distrito Federal corroborate this result and add more insights to policy discussion.
Keywords: O15; J13; I38; 330; adolescent mothers; conditional cash transfers; schooling attendance